The Role of Regulation in the Development of Sharia Fintech: A Review of Contemporary Islamic Economic Law - Istianah Zainal Asyiqin; Irvan Mareto; Manuel Beltrán Genovés (Yayasan Adra Karima Hubbi, 2024)
This research explores the intricate relationship between regulation and the development of Sharia-compliant financial technology (fintech) within the framework of contemporary Islamic economic law. As Sharia fintech emerges as a significant sector in the global financial landscape, the alignment of innovative financial technologies with Sharia principles becomes crucial. The paper delves into the challenges and opportunities posed by regulatory fragmentation, the impact of technological advancements, and the importance of international coordination and harmonization. Regulatory fragmentation, characterized by diverse interpretations of Sharia law and differing national regulations, complicates cross-border operations, stifles innovation, and leads to a lack of standardization in financial products. Technological advancements, such as blockchain, artificial intelligence, and digital currencies, offer immense potential for enhancing transparency, efficiency, and inclusivity in Islamic finance but also introduce complex regulatory challenges. The paper argues for a proactive and collaborative regulatory approach, emphasizing the need for international standards and greater harmonization to ensure that Sharia fintech can thrive globally. By addressing these issues, the paper highlights the critical role of regulation in shaping the future of Sharia-compliant fintech, ensuring its growth, scalability, and adherence to Islamic ethical principles.